FACE OF SOCIAL SCIENCES IN CONTEMPORARY THE ISLAMIC REPUBLIC OF IRAN - supratman, supratman supratman (Universitas Hasanuddin, 2021)
The Islamic Republic of Iran is a country completely different from all countries in the world in all aspects. Understanding Iran must be with Iran's own social sciences. Descriptive and analytical methods, as well as a collection of information via the internet and libraries in this paper, analyze the existence of social sciences in Iran, the development process and face of social sciences in contemporary Iran. This paper identified; A). The ancient Persian civilization was familiar with the concept of social sciences. B). the communist school of thought and movement had been a part of life in the government of Shah Muhammad Reza Pahlevi. Keywords; Social Science, Iran, Culture, Philosophy, Islam.